Spectroscopic orbits and variations of RS Ophiuchi - Brandi, Estela (2009)
The aims of our study are to improve the orbital elements of the giant, and to derive the spectroscopic orbit for the white dwarf companion. Spectral variations related to the 2006 outburst are also studied. Methods. We performed an analysis of about seventy optical and near infrared spectra of RS Oph that were acquired between 1998 and June 2008. The spectroscopic orbits have been obtained by measuring the radial velocities of the cool component absorption lines and the broad Hα emission wings, which seem to be associated with the hot component. A set of cF-type absorption lines were also analyzed for a possible connection with the hot component motion. Results. A new period of 453.6 days, and a mass ratio, q = Mg/Mh = 0.59 ± 0.05, were determined. Assuming a massive white dwarf as the hot component (Mh = 1.2 − 1.4M⊙) the red giant mass is Mg = 0.68 − 0.80M⊙ and the orbit inclination, i = 49◦ − 52◦. The cF-type lines are not associated with either binary component, and are most likely formed in the material streaming towards the hot component. We also confirm the presence of the Li I doublet in RS Oph and its radial velocities fit very well the M-giant radial velocity curve. Regardless of the mechanism involved to produce lithium, its origin is most likely from within the cool giant rather than material captured by the giant at the time of the nova explosion. The quiescent spectra reveal a correlation of the HI and He I emission line fluxes with the monochromatic magnitudes at 4800 Å indicating that the hot component activity is responsible for those flux variations. We also discuss the spectral characteristics around 54–55 and 240 days after the 2006 outburst. In April 2006 most of the emission lines present a broad pedestal with a strong and narrow component at about -20 kms−1 and two other extended emission components at -200 and +150 kms−1. These components could originate in a bipolar gas outflow supporting the model of a bipolar shock-heated shell expanding through the cool component wind perpendicularly to the binary orbital plane. Our observations also indicate that the cF absorption system was disrupted during the outburst, and restored about 240 days after the outburst, which is consistent with the resumption of accretion.